National Literature - Павлович, Тетяна Іванівна (Технодрук, 2021)
National Literature reveals historical, political, literary, religious, and mythic contexts for the study of Literature as well as a number of key concepts and theoretical issues in literary studies. The course focuses on theory and interpretation – the reasons for literary change, the definitions of periods, and the evolution of styles, conventions, and genres. Throughout its history, National literature has always resisted short-lived trends and subsuming ideologies. By delving into the theoretical bases of practical criticism, the course reexamines the relations between past works and present critical and theoretical needs.
Keywords: навчальний посібник для 4 курсу